Photoelectrocatalytic H2 evolution from integrated photocatalysts adsorbed on NiO. Issue 1 (12th October 2018) - Põldme, Nils; O'Reilly, Laura; Fletcher, Ian; Portoles, Jose; Sazanovich, Igor V.; Towrie, Michael; Long, Conor; Vos, Johannes G.; Pryce, Mary T.; Gibson, Elizabeth A.
Abstract : A new approach to increasing the faradaic efficiency of dye-sensitised photocathodes for H2 evolution from water is described, using integrated photocatalysts based on a ruthenium 4, 4′-diethoxycarboxy-2, 2′-bipyridine chromophore linked via terpyridine or triazole to a Pd or Pt-based H + reduction catalyst. Abstract : A new approach to increasing the faradaic efficiency of dye-sensitised photocathodes for H2 evolution from water, using integrated photocatalysts, furnished with ester groups on the peripheral ligands, [Ru(decb)2 (bpt)PdCl(H2 O)](PF6 )2 (1 ) and [Ru(decb)2 (2, 5-bpp)PtI(CH3 CN)](PF6 )2 (2 ), (decb = 4, 4′-diethylcarboxy-2, 2′-bipyridine, bpp = 2, 2':5′, 2′′-terpyridine, bpt = 3, 5-bis(2-pyridyl)-1, 2, 4-triazole) is described. Overall, 1 |NiO is superior to previously reported photocathodes, producing photocurrent densities of 30–35 μA cm −2 at an applied bias of −0.2 V vs. Ag/AgCl over 1 hour of continuous white light irradiation, resulting in the generation of 0.41 μmol h −1 cm −2 of H2 with faradaic efficiencies of up to 90%. Furthermore, surface analysis of the photocathodes before and after photoelectrocatalysis revealed that the ruthenium bipyridyl chromophore and Pd catalytic centre (1 ) were photochemically stable, highlighting the benefits of the approach towards robust, hybrid solar-to-fuel devices.